Ropinirole, a potential drug for systematic repositioning based on side effect profile for management and treatment of breast cancer. (November 2020) - Rymbai, Emdormi; Sugumar, Deepa; Saravanan, J.; Divakar, S.
Abstract: Drug repositioning offers two main advantages in drug discovery – the process is less tedious and less costly. In the past, many drugs like thalidomide and sildenafil were successfully repositioned but the process was entirely serendipitous. These days drug repositioning is widely accepted as an alternate method of drug discovery and the process is based on building a strong hypothesis guided by systematic computational and experimental methods. One of the methods used in drug repositioning is based on shared side effects by drugs of different pharmacological categories. This method rests on the principle that drugs that share side effects might also share common biological targets and therefore same pharmacological indications. Old drugs can be repositioned for new uses by identifying the shared side effects of existing drugs and by modulating their chemical structure if required. Breast cancer is the most common type of cancer in women and the second leading cause of death worldwide after lung cancer in both men and women. Letrozole, an aromatase inhibitor, is used in the treatment of advanced, recurrent and metastatic breast cancer in post-menopausal women. Identification of drugs that share side effects with letrozole might help us to identify a potential drug for repositioning in the treatment of breast cancer. Ropinirole, a dopaminergic agonist was found to share the maximum number of side effects with letrozole. Studies have proposed that dopaminergic agonists induce apoptosis in breast, colon, ovarian cancer cells and leukemia neuroblastoma. This is consistent with our hypothesis that ropinirole that shares the maximum number of side effects with letrozole might be effective in the management of breast cancer. This hypothesis was further validated by preliminary molecular docking and in-vitro cell-line studies.